ANALISIS PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA) - Randi Febrian; Tertiarto Wahyudi; Ahmad Subeki (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
This study aims to analyze the effect of tax planning and deferred tax expense to earnings management. The data used in this study is data based on annual financial statements of manufacturing sector companies listed on the Indonesia Stock Exchange period 2013-2015. Sampling method using purposive sampling. The number of manufacturing companies sampled as many as 40 companies for three years, so the total sample of research is 120. The method of analysis used is multiple linear regression analysis. Based on the results of this study shows that partially tax planning has a significant effect on earnings management with a significance of 0.000. Deferred tax expense does not have a significant effect on earnings management with significance of 0.412. While simultaneous tax planning and deferred tax burden have significant effect to earnings management with significance equal to 0,001.